Multidrug resistance organisms (MDRO) infection and multidimensional approaches as predictors of mortality in complicated intra-abdominal infection - Suryanto, Antonius; Adeodatus Yuda Handaya; Sumadi Lukman Anwar; Stefani Candra Firmanti (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Complicated intra-abdominal infection (cIAI) is a frequently encountered emergency surgery case with a high mortality rate. While the mortality scoring system in cIAI has been widely adopted, its accuracy has not been fully optimized, yet. The study aimed to analyze the prognostic value of APACHE II, MPI, CCI, MODS, and MDRO infections in the mortality of patients with cIAI. A prospective cohort observational study was conducted on cIAI patients who underwent laparotomy procedures in November 2023 to July 2024 at Dr. Sardjito Hospital, Yogyakarta. Microbiological examinations in the form of identification and antibiotic sensitivity tests were carried out on intra-abdominal specimens using Vitek II. Information on demographic characteristics, clinical presentation, laboratory characteristics, and mortality outcomes was collected by following patients for 30 d of post-laparotomy care until the patient died or was discharged from the hospital. Statistical analysis was carried out using a t test, X2, and ROC curve, determining the cut-off point of the score, sensitivity, specificity, PPV, NPV, and accuracy of each prognostic variable. Out of the 91 cIAI patients who underwent laparotomy, mortality was observed in 28.6% of them. MDRO infection was identified in 52.7% of the subjects. Significant factors affecting mortality were APACHE II scores (p=0.00), MPI scores (p=0.00), MODS scores (p=0.00), and MDRO infection (p=0.03). The prognostic performance of mortality based on the AUC, sensitivity, and specificity scores were as follows: APACHE II (AUC=0.938; sensitivity=88.5%; specificity=86.2%), MPI (AUC=0.920; sensitivity=92.3%; specificity=81.5%), MODS (AUC=0.916; sensitivity=76.9%; specificity=93.8%), CCI (AUC= 0.582; sensitivity=61.5%; specificity=56.9%), and MDRO infection (AUC= 0.623; sensitivity=61.5%; specificity=63.1%). In conclusion, the APACHE II, MPI, MODS scores showed strong performance in predicting the mortality of cIAI patients. MDRO infection is significant determinant for mortality but has weak diagnostic value. Developing new algorithms that consider comprehensive factors including agents, hosts, and environments will enhance the accuracy of assessing mortality in these patients.